Relationship between job involvement, leader-member exchange, and innovative behavior of public librarians. (June 2020) - Peng, Yu-Ping
Public library leaders require librarians to exhibit markedly high job involvement and notably innovative behaviors to maintain pace with rapidly varying environments. The study examined the relationships between the job involvement, leader–member exchange, and innovative behavior of public librarians through structural equation modeling. The finding identified the antecedents (job involvement and leader–member exchange ) of innovation behavior. Leader–member exchange was a significant moderator of the job involvement–innovative behavior relationship. The findings can enhance understanding of these relationships in the public library context. Finally, the study provided suggestions for leaders within the librarianship profession to develop for themselves and their subordinates.